Optimism and Pessimism and their Relationship to Stressful Life Events among Female General Education Retirees at Al-Ahsa Governorate - Alduhaish, Rowida Adel (Journal of Educational and Psychological Sciences, 2021)
The study aimed at identifying the relationship between optimism and pessimism and the stressful life events of the public education female retirees in Al-Ahsa governorate. It also aimed to identify the level of optimism and pessimism of the female retirees, and to identify the differences in degrees of optimism and pessimism according to the following variables: Marital status, economic status, age and type of retirement. The researcher used the comparative, linking and descriptive approach to discuss this type of relationships, using the Arab list of optimism and pessimism by Abdulkhaliq (1996) and a stresses scale of life events for the elderly by Zaatar and Abo Alkhair (1999). The sample of the study consisted of (250) female retirees, and they were chosen in a stratified random sample. The application was conducted in the first semester of the year 2020, after ensuring the validity and consistency of the study tools. After application, the Statistical Package (SPSS) processed the data. results revealed that there is a statistically significant negative relationship between optimism and stressful life events. There is also a positive relationship with statistical significance between pessimism and stressful life events, high level of optimism and low level of pessimism. The study also showed that there are no statistically significant differences in optimism and pessimism among female due to changes in the marital/economic status and age. There are statistically significant differences in optimism and pessimism due to the type of retirement, as optimism was associated with early retirement, and pessimism was associated with mandatory retirement.
Keywords: Optimism; Pessimism; Stress; retirees; public education